2004
DOI: 10.1890/03-0492
|View full text |Cite
|
Sign up to set email alerts
|

Resource Level and Reproductive Frequency in Female Four-Toed Salamanders, Hemidactylium Scutatum

Abstract: Many species of vertebrate animals skip reproduction in some years. We studied the pattern of reproduction exhibited by female four-toed salamanders (Hemidactylium scutatum). Data from a 10-year field study showed that females reproduced in sequential years with a frequency of 0.56 but skipped one or more years of reproduction with a frequency of 0.44. This pattern was not correlated with whether a female attended or deserted her nest. When females skipped reproduction, they had higher growth, which can transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Only a few cases have been documented in amphibians, in egg-guarding salamanders such as Hemidactylium scutatum (Harris et al, '95;Harris and Ludwig, 2004) and Ambystoma opacum (Kaplan and Crump, '78;Croshaw and Scott, 2005). In these species, females oviposit eggs in communal nests and some females remain with the clutches until hatching, and there is no costly, post-paritive, maternal provision of nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases have been documented in amphibians, in egg-guarding salamanders such as Hemidactylium scutatum (Harris et al, '95;Harris and Ludwig, 2004) and Ambystoma opacum (Kaplan and Crump, '78;Croshaw and Scott, 2005). In these species, females oviposit eggs in communal nests and some females remain with the clutches until hatching, and there is no costly, post-paritive, maternal provision of nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Milanovich et al [132] documented that, in the western slimy salamander (Plethodon albagula), the amount of precipitation one year prior to oviposition was correlated with average clutch size in the subsequent year. Food availability has been shown to affect traits related to individual fitness in other species of salamanders as well (Figure 3; [133,134]). …”
Section: Food Availabilitymentioning
confidence: 99%
“…Harris and Ludwig (2004) experimentally demonstrated that reproductive frequency of plethodontid salamanders (Hemidactylium scutatum) varied with resource levels, and more females oviposited in consecutive years under high food treatments. Reproductive frequency of female Plethodon cinereus varies depending on geographic locality.…”
Section: Introductionmentioning
confidence: 99%